Harnessing daylight potentials as a tool for visual and thermal comfort in residential buildings - Tukur, Rukayyatu Bashiru (2013)
Architects have a responsibility to understand clearly, and sensibly plan housing units and ultimately the cities so as to achieve a sustainable whole. By so doing, these professionals cannot afford to neglect any aspect of the housing envelope, nor consider it in part or as a whole as un-important. It is for this purpose, that we look at the aspects of harnessing daylight through a variety of systems and methods so as to make best use of this free and in-exhaustible commodity for both visual and thermal comfort. The major question which this thesis attempted to answer was to find a means of improving visual and thermal comfort in our homes while at the same time reducing our fossil fuel emissions. It was to this end that attention was turned towards the earth‟s major source of energy and to see how best to harness this resource and put it to passive use in the best possible non-intrusive manner. This thesis as a whole, attempted to evaluate existing lighting and thermal devices with an aim to enhancing them as well as suggesting novel devices to replace the existing ones. This thesis reviewed and tested the performance of solar evacuators, optical rods known to have high transmittance, as well as light pipes to see their applicability in residential dwellings in terms of the provision and lighting and heating within the residential buildings. Studies were also done to determine the effect of the combination of two technologies on the same platform i.e. light-pipes combined with light rod, as well as light rods combined with solar evacuators to ascertain and enhance their viability. These tests were carried out in three ways, viz; laboratory tests, outdoor tests as well as field tests on existing real life applications on the singular technology in use as a base-line for assessing the new technologies.